Sistem Informasi Manajemen Berkas Perkara Berbasis Web Pada Kejaksaan Negeri Merangin - Setiawan , Irmawan; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2022)
The Merangin District Prosecutor's Office is a law enforcement agency that is required to play a greater role in enforcing the law. In the current file data management system, it is still done manually, that is, every incoming case file is recorded in the register book and archived into the file cabinet. This makes it difficult for the process of searching for file data and compiling case files which will be processed by the prosecutor's office and making reports. Based on the existing problems, a case file management system is needed in order to assist the Merangin District Attorney in overcoming the existing problems. The purpose of this study is to design a prototype case file management system using system modeling tools, namely UML and the diagrams used include use case diagrams, activity diagrams and class diagrams. The results of this study are a prototype case file management system design that can be applied by the Merangin District Attorney to help expedite case management and provide maximum service to the public.